Preferensi Mahasiswa Dalam Memilih Organisasi - Fitria Ana Lestari; Pardiman Pardiman; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Organization is any form of union between two or more people who work together for common purposes and are formally bound in a fellowship in which there is always a relationship between a person or group of people called leaders and one or other people called subordinates (Hari Sulaksono, 2015: 1). The purpose of this study was to determine Student Preferences in Choosing Organizations in UNISMA student activists. The sample in this study was 88 respondents with the technique used in this study purposive sampling. The results of this study show that: 1. The combination of attributes that are considered the most important is at the social level, Organizational Goals, Perceptions of seniors, Values of Responsibility and honesty 2. Attributes based on interests are organizational characteristics 3. The most important attribute level is the image of the organization in the values of responsibility and honesty, organizational characteristics are found in organizational goals, motivation from seniors is found in perceptions of seniors, and development is in social attitudes. Keyword : Preferences, Organizational Image, Organizational Characteristics, Motivation From Seniors, Self-Development.